Peningkatan Saturasi Oksigen pada Pasien Congestive Heart Failure dengan Pemberian Posisi Semi Fowler - Desty Fajariah; Veroneka Yosefpa Windahandayani; Keristina Ajul (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Congestive Heart Failure (CHF) is a chronic condition that causes impaired heart function in pumping blood, which can reduce oxygen levels in the body. The increasing incidence of CHF in Indonesia requires appropriate treatment to improve patient health status. One of the evidence-based practice (EBP) interventions that can be applied is the provision of a semi-Fowler position to increase oxygen saturation in CHF patients. This study aims to determine the effectiveness of providing a semi-Fowler position in increasing oxygen saturation in CHF patients undergoing treatment in the inpatient room of Siti Fatimah Hospital, South Sumatra Province. This study uses a qualitative approach with a descriptive case study method on three CHF patients who meet the inclusion and exclusion criteria. Data were collected through interviews, observations, and oxygen saturation measurements using an oximeter before and after the semi-Fowler position intervention for three days. The results showed an increase in oxygen saturation after the application of the semi-Fowler position in all respondents. In Mr. M, there was an increase in average oxygen saturation of 6%, in Mr. N by 3.3%, and in Mrs. N by 4.7%.